Heterologous Expression and Rational Design of l-asparaginase from Rhizomucor miehei to Improve Thermostability - Xian Zhang; Zhi Wang; Yimai Wang; Xu Li; Manchi Zhu; Hengwei Zhang; Meijuan Xu; Taowei Yang; Zhiming Rao (Biology, 2021)
l-asparaginase (EC 3.5.1.1) hydrolyzes l-asparagine to produce l-aspartate and ammonia and is widely found in microorganisms, plants, and some rodent sera. l-asparaginase used for industrial production should have good thermostability. We heterologously expressed l-asparaginase from Rhizomucor miehei, selected nine loci for site-directed mutagenesis by rational design, and obtained two mutants with significantly improved thermostability. The optimal temperature of mutants S302I and S302M was 50 °C. After incubating the mutant and wild-type enzymes at 45 °C for 35 h, the residual activity of the wild-type enzyme (WT) was only about 10%. In contrast, the residual activity of S302I and S302M was more than 50%. After combination mutagenesis, Bacillus subtilis 168-pMA5-A344E/S302I was constructed using the food-safe host strain B. subtilis 168. Additionally, a 5′ untranslated region (UTR) modification strategy was adopted to enhance the expression level of R. miehei-derived l-asparaginase in B. subtilis. In a 5-L fermenter scale-up experiment, the enzyme activity of recombinant B. subtilis 168-pMA5-UTR-A344E/S302I reached 521.9 U·mL−1 by fed-batch fermentation.